Manhood, marriage & mischief : Rembrandt's 'Night watch' and other Dutch group portraits - Berger, Harry (Fordham University Press, 2007)
A study of the theory and practice of seventeenth-century Dutch group portraits, 'Manhood, Marriage, & Mischief' offers an account of the genre's comic and ironic features, which it treats as comments on the social context of portrait sitters who are husbands and householders as well as members of civic and proto-military organizations.